Analisis Efektivitas Bangunan Pengendali Sedimen dalam Mengatasi Sedimentasi dan Erosi di Sungai Namo dengan Simulasi HEC-RAS 2D - Hannah Nuril Layaliya; Joko Nugroho (Departement of Mathematics Education, 2024)
Flash floods occurred on August 13, 2019, hitting Namo Village, Kulawi Sub-district, Sigi Regency, Central Sulawesi Province, causing many losses, such as washed away houses and breaking the Palu-Kulawi access road. The flash flood was caused by high rainfall with a duration of 3 hours, bringing landslide material in the form of rocks and wood from upstream. To overcome this result, the construction of sediment control structures consisting of sabo dams, box culvert bridges, groundsills, and channel work in the form of concrete embankments was carried out. This study aims to compare the effectiveness of sediment control buildings against existing conditions and after the implementation of development by simulating sediment transport with 2D HEC-RAS. With the Wilcock and Crowe transport equation, the results show that with a 100-year return period flood discharge (Q100), the existing conditions in the area affected by the sediment control building are dominated by erosion, while in the downstream area, sedimentation is dominated. After handling, the simulation results show that in the area affected by the building, there is an increase in erosion of 48,948.98 m3 or a decrease in building effectiveness of 79.34%. Meanwhile, the downstream area experienced an increase in sedimentation of 92,906.02 m3 or an increase in effectiveness of 189.94%. Based on this simulation, there is still a need for handling to reduce the level of erosion in the upstream area by adding a control building.